Current perspectives in hypertrophic cardiomyopathy with the focus on patients in the Finnish population: a review. (2nd October 2016) - Kuusisto, Johanna; Sipola, Petri; Jääskeläinen, Pertti; Naukkarinen, Anita
Abstract: Hypertrophic cardiomyopathy (HCM) is the most common inherited heart disease, with the prevalence of about 1/500. During the last two decades, the knowledge of the etiology, pathogenesis, risk stratification and prevention of sudden death in HCM has substantially advanced. Most often, HCM is familial and caused by mutations in sarcomere genes, inherited in an autosomal dominant manner. In Finland, genetic background of HCM is unique, with a few founder mutations in cardiac sarcomere genes accounting for a considerable proportion of the disease. Pathogenic mechanisms induced by disease-causing mutations are still poorly understood, although alterations in intracellular calcium handling and inefficient generation of contractile force in myocytes are considered key features in triggering the hypertrophic response. Clinical features of the disease are highly variable from no symptoms to the spectrum of exertional dyspnea, angina, palpitations, syncope and sudden death. In the current patient care, implantable cardioverter defibrillators (ICDs) are successfully used to prevent sudden cardiac death in high risk subjects. Targeted genetic testing is recommended to confirm the diagnosis in patients with HCM and to identify family members with the disease. Future research is needed to elucidate key cellular mechanisms leading to HCM, which may allow specific prevention and treatment of the disease. Key messages: Hypertrophic cardiomyopathy, most often caused by defects in sarcomere genes, is the most common inherited heart disease, and a common cause of sudden cardiac death (SCD) in athletes and young subjects. Cardiac imaging, ECG and genetic testing are pivotal in the diagnosis of the disease in patients and first-degree relatives. Implantable cardioverter defibrillators in patients with high risk for SCD and tailored pharmacotherapy are efficient tools in patient care, but so far, exact mechanisms leading to cardiac hypertrophy in HCM are only partially understood, and there is no curative treatment for the disease.